Distance education in the use of cloud educational technologies as the basis of career guidance for applicants - M. I. Sadovyi; O. M. Tryfonova (Academy of Cognitive and Natural Sciences, 2013)
According to the National Doctrine of Education Development in Ukraine, the urgent task is to ensure accessibility of quality lifelong learning for all citizens. In the current conditions of the development of educational space in Ukraine, distance education meets the condition of lifelong learning to the greatest extent. At the same time, the development of technology and technology contributes to the rapid development of educational ICT, in particular - the cloud. Therefore, the problem of organizing distance learning in modern conditions has arisen. Cloud ICTs provide qualitatively new opportunities for education, in particular distance learning. With the development of computer learning tools, the teaching methodology is also changing: new opportunities appear, new approaches - learning becomes more communicative and modern.